2018
DOI: 10.15809/irriga.2016v1n01p191-204
|View full text |Cite
|
Sign up to set email alerts
|

Ação De Bioestimulante No Desenvolvimento Inicial Do Milho Doce Submetido Ao Estresse Salino

Abstract: AÇÃO DE BIOESTIMULANTE NO DESENVOLVIMENTO INICIAL DO MILHO DOCE SUBMETIDO AO ESTRESSE SALINO  RAFAELA CRISTINA DA CUNHA1; FRANCISCO DE ASSIS DE OLIVEIRA1; MARIA WILLIANE DE LIMA SOUZA1; JOSÉ FRANCISMAR DE MEDEIROS1; LUAN ALVES LIMA1; MYCHELLE KARLA TEIXEIRA DE OLIVEIRA1 1 Departamento de Ciências Ambientais e Tecnológicas, UFERSA; Avenida Francisco Mota, 572, 59625-900, Bairro Costa e Silva, Mossoró, RN, Brasil, e-mail: rafacris_dantas@hotmail.com; thikaoamigao@ufersa.edu.br; williane-lima@hotmail.com; jfmedei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
3
0
4
Order By: Relevance
“…However, in plants irrigated with high-salinity water, a quadratic behavior was observed, and highest dry matter accumulation (23.31 mg) was found at phytohormone concentration of 27.6 µM L -1 ( Figure 2B). Cunha et al (2016) andSouza Neta et al (2018) observed that the use of the biostimulant Stimulate®, composed of a mixture of substances [0.005% of indolebutyric acid (auxin), 0.009% of kinetin (cytokinin) and 0.005% of gibberellic acid (gibberellin)], was not efficient at mitigating the effect of salinity on sweet corn and gherkin, and found benefits only in plants grown in the absence of salt stress. The opposite was observed in the present study, which may be related to the low concentration of phytohormones in the biostimulant evaluated by these authors.…”
Section: Resultsmentioning
confidence: 99%
“…However, in plants irrigated with high-salinity water, a quadratic behavior was observed, and highest dry matter accumulation (23.31 mg) was found at phytohormone concentration of 27.6 µM L -1 ( Figure 2B). Cunha et al (2016) andSouza Neta et al (2018) observed that the use of the biostimulant Stimulate®, composed of a mixture of substances [0.005% of indolebutyric acid (auxin), 0.009% of kinetin (cytokinin) and 0.005% of gibberellic acid (gibberellin)], was not efficient at mitigating the effect of salinity on sweet corn and gherkin, and found benefits only in plants grown in the absence of salt stress. The opposite was observed in the present study, which may be related to the low concentration of phytohormones in the biostimulant evaluated by these authors.…”
Section: Resultsmentioning
confidence: 99%
“…As plantas em estresse salino limitam o seu crescimento, pois, a pressão osmótica do meio aumenta com a presença dos sais e, consequentemente, haverá uma redução da água disponível para o vegetal, afetando a divisão celular e o alongamento das células (OLIVEIRA et al, 2014). Cunha et al (2016) observaram que a altura de plantas de milho foi afetada negativamente pela água de maior salinidade. Resultados similares ao do presente trabalho também foram obtidos por Dias et al (2017), que verificaram que o crescimento em altura das plantas de algodão foi prejudicado com o aumento da condutividade elétrica da água de irrigação em diferentes épocas de avaliação.…”
Section: Resultsunclassified
“…De acordo com Prisco e Gomes Filho (2010), essas alterações morfológicas ocorrem em razão do desbalanço hídrico, nutricional e hormonal, causado pelo excesso de sais solúveis presentes na água de irrigação. Cunha et al (2016) em trabalhos com plantas de milho doce, averiguaram que com o aumento da condutividade elétrica da água houve redução no diâmetro caulinar. No entanto, contrariando esse resultado, Sousa et al (2012) verificaram que os níveis crescentes de sais da água de irrigação não exerceram efeitos significativos sobre o diâmetro do colmo em plantas de milho.…”
Section: Resultsunclassified
“…With the increase in its exploitation by producers, the adoption of new technologies such as the use of biostimulants, stands as a good option to optimize production in different crops (Cunha et al, 2016). The application of biostimulants can morphologically change the plant organs, in which their growth and development are inhibited, in a way that meristematic activity is influenced, resulting in a more uniform formation and harvest of the seeds (Jesus Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%